Literary Journalism Training to Enhance the Imaginative Thinking of Students at SMKN 2 Garut - Ayies Devin Seftian; Achmad Wildan Kurnawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The background of this community service activity is a response to the use of technology and social media that affects Indonesian students, causing them to focus more on technology usage. This phenomenon has diminished their interest in honing writing skills and imaginative thinking, as observed at SMKN 2 Garut. The objective of this initiative is to expand knowledge of literary journalism, enhance the writing and imaginative skills of students at SMKN 2 Garut, and prepare them for academic and professional environments. The training method employs a combination of Participatory Action Research (PAR), Target Situation Analysis (TSA), and Project-based Learning (PBL), involving the introduction of literary journalism concepts and the practice of writing literary works. The results show a significant improvement in students' understanding and skills in expressing ideas imaginatively through literary journalism writing. This training also positively contributes to developing students' writing skills and imaginative thinking as part of their education. The activity successfully increased students' knowledge of literary journalism and enhanced their imagination, resulting in good literary works by leveraging students' thinking and creativity.